Guide to the essentials in emergency medicine - Ooi, Shirley; Manning, Peter (McGraw-Hill, 2015)
This book focuses on the practical management of the most life-threatening and common conditions encountered by emergency physicians. It is designed to offer a balanced viewpoint advocating the tenets of evidence-based medicine. This second edition preserves several of its predecessor's hallmark features. Easy-to-read format: clinical descriptions are presented succinctly and problems are introduced with the same symptom-based approach in Section One. Popular sections such as Caveats, covering the pitfalls likely to be encountered in medical practice, and Special Tips for GPs are retained. New features of this second edition include: Twenty new chapters, Thorough revision of the text for more content coverage, easier reading, and reflection of the latest evidence, Reorganisation of Section Two into specific systems for ease of reading and revision for exams, Inclusion of coloured photographs Addition of further illustrations, ECGs, plain radiographs, CT scans and ultrasound images.